Ações de alimentação e nutrição e de educação permanente no cuidado a obesidade na atenção primária à saúde de municípios do estado da Paraíba - Menezes, Micaela de Sousa (2024)
Introduction: Obesity is considered a global epidemic. Changes in the population's lifestyle habits, such as the increase in sedentary lifestyle and the consumption of high-calorie foods, contribute to the high prevalence of obesity throughout the world. Actions to Promote Adequate and Healthy Food (PAAS) aim to promote the population's dietary quality through the implementation of actions distributed in different sectors of the country. Primary Health Care (PHC) is considered a strategic field for the application of these actions, in addition to playing a prominent role in carrying out food and nutritional surveillance (VAN) actions and in caring for overweight and obese users. The qualification of teams is essential for the effectiveness of the implementation of programs and actions related to food and nutrition with the aim of contributing to the implementation of actions to prevent and care for eating disorders and disorders in the population. Objective: To describe the types of food and nutrition actions carried out in primary health care, the provision of permanent education in obesity care and its association with the implementation of lines of care and food surveillance in municipalities in Paraíba. Methods: This is a cross-sectional study, nested within a national population-based study. Data collection occurred through the application of semi-structured and self-administered questionnaires, made available remotely through the SurveyMonkey® digital platform. The study used only a sample of the aforementioned instrument. Variables related to the responding professionals, the types of actions to promote adequate and healthy eating and the provision of ongoing education in obesity care and their association with food surveillance actions and implementation of lines of care were evaluated. Data were analyzed using the R software. Descriptive analysis was performed, using absolute and relative frequency, for qualitative variables and to test the association between variables, Pearson's chi-square test and Fisher's exact test were used, when necessary. . The level of statistical significance adopted was 5%. Results: The type of community PAAS action was the approach most carried out by health teams, followed by the type of group action, with nurses, doctors and nutritionists being the ones who most participate in these actions. The carrying out of permanent education actions aimed at professionals was verified, and in relation to their frequency, it was below expectations, an association was verified between the carrying out of permanent education actions and the carrying out of VAN. Conclusion: Community and group actions to promote adequate and healthy eating are the most carried out by teams, the frequency of continuing education actions aimed at these professionals was well below expectations. The results indicated an association between continuing education and carrying out food and nutritional surveillance actions. The need for more studies is highlighted to evaluate which tools are being used in PAAS actions and user adherence to better understand the scenario in the State.